A temperature gradient may support mother‐infant thermal identification and communication in the breast crawl from birth to breastfeeding. (26th July 2017) - Zanardo, Vincenzo; Volpe, Francesca; de Luca, Federico; Straface, Gianluca
Abstract: Aim: The human female's nipple‐areolar complex (NAC) is the point of arrival of a natural progression from birth to breastfeeding, linked to functional, chemical and biophysical cues that promote the breast crawl soon after birth. We investigated the thermal gradient generated by the lips of the neonate and warmth of the NAC, which may drive the infant directly to the nipple. Methods: We prospectively studied 41 full‐term singleton infants and their mothers at the Policlinico Abano Terme, Italy, between January 1, 2015, and February 28, 2015. NAC and breast quadrant temperatures were assessed 6 ± 2 hours prepartum and one and two days postpartum, together with the neonates' lip temperature. Results: The temperature of the neonates' lips was significantly lower than the forehead temperature on days one and two postpartum (delta = −1.24°C, p < 0.001 and delta = −1.02°C, p < 0.001, respectively). Thus, the thermal gradient between the NAC and the neonates' lips was −1.66 ± 1.07°C on day one (p < 0.001) and −1.68 ± 0.63°C (p < 0.001) on day two postpartum. Conclusion: These findings demonstrate, for the first time, that a temperature gradient may support mother‐infant thermal identification and communication in the breast crawl and in the natural progression of the continuum from birth to breastfeeding.